Fallopian tube initiation of high grade serous ovarian cancer and ovarian metastasis: Mechanisms and therapeutic implications. (28th April 2020) - Bergsten, Tova M.; Burdette, Joanna E.; Dean, Matthew
Abstract: Ovarian cancer is the most lethal gynecologic malignancy and the fifth leading cause of cancer-related death in women. Although outcomes have improved in recent years, there remains an unmet clinical need to understand the early pathogenesis of ovarian cancer in order to identify new diagnostic approaches and agents of chemoprevention and chemotherapy. While high grade serous ovarian cancer (HGSOC), the most abundant histotype, was initially thought to arise from the ovarian surface epithelium, there is an increasing body of evidence suggesting that HGSOC originates in the fallopian tube. With this new understanding of cell of origin, understanding of disease development requires analysis with a novel perspective. Currently, factors that drive the initiation and migration of dysplastic tubal epithelial cells from the fallopian tube to the ovary are not yet fully defined. These factors include common mutations to fallopian tube epithelial cells, as well as factors originating from both the fallopian tube and ovary which are capable of inducing transformation and dissemination in said cells. Here, we review these changes, their causative agents, and various potential means of intervention. Highlights: Ovarian cancer is the most lethal gynecologic malignancy. Fallopian tube epithelium is a source for high grade ovarian cancer. New analysis of transformation and metastasis can improve diagnosis and treatment.